THE INFLUENCE OF CONDITIONS OF THE HEAT TREATMENT OFALUMINUMALLOYS - Stoicanescu, Maria (European Scientific Journal, ESJ, 2015)
Work was followed in determining the optimum parameters of heat treatment of deformable aluminum alloy, regarding both the hardening and aging. The tests were performed on two brands of deformable alloys, both after the usual process and electromagnetic field.